Efficacy and safety of guanfacine extended‐release in Japanese adults with attention‐deficit/hyperactivity disorder: Exploratory post hoc subgroup analyses of a randomized, double‐blind, placebo‐controlled study. Issue 1 (10th December 2020) - Naya, Noriyuki; Sakai, Chika; Okutsu, Daiki; Kiguchi, Ryo; Fujiwara, Masakazu; Tsuji, Toshinaga; Iwanami, Akira
Abstract: Aim: Previously, we reported on the efficacy and safety of guanfacine extended‐release (GXR) in Japanese adults with attention‐deficit/hyperactivity disorder (ADHD) from a phase 3, double‐blind, placebo‐controlled, randomized trial. In this exploratory post hoc analysis, we assessed the efficacy and/or safety of GXR in the following subgroups: ADHD‐combined (ADHD‐C) and ADHD‐predominantly inattentive (ADHD‐I) subtypes, age (≥31, <31 years), sex (male, female), and body weight (≥50, <50 kg). Methods: The primary efficacy endpoint was change from baseline in the Japanese version of the investigator‐rated ADHD‐Rating Scale‐IV (ADHD‐RS‐IV) with adult prompts (total scores) at week 10. Results: The efficacy analysis population included 200 patients (GXR, 100; placebo, 100). ADHD‐RS‐IV total score effect sizes (GXR vs placebo) were similar across all subgroups (total population: 0.52, ADHD‐C: 0.51, ADHD‐I: 0.52, ≥31 years: 0.61, <31 years: 0.47, male: 0.50, female: 0.57). There were no major differences in the incidence/types of treatment‐emergent adverse events (TEAEs) across the subgroups. The incidence of significant TEAEs (34.3%, 10.6%) and TEAEs leading to discontinuation (34.3%, 12.1%) were approximately three times higher in females than males, respectively. The incidence of TEAEs in patients weighing <50 kg and ≥50 kg was 100% and 73.6% during dose optimization and 40% and 24.4% during the maintenance period, respectively. Conclusion: Findings from this post hoc analysis in adults with ADHD support the efficacy and safety of GXR regardless of ADHD subtype, age, or sex and suggest that careful monitoring for TEAEs and GXR dose optimization is considered for all patients, as needed. Abstract : In this exploratory post hoc analysis, we assessed the efficacy and/or safety of guanfacine extended release (GXR) in the following subgroups: attention‐deficit/hyperactivity disorder (ADHD) subtypes (ADHD‐combined, ADHD‐predominantly inattentive), age (≥31 years, <31 years), sex (male, female), and body weight (<50 kg, ≥50 kg). ADHD‐Rating Scale‐IV with adult prompts total score effect sizes (GXR vs placebo at 10 weeks) were similar across all subgroups. The findings support the efficacy and safety of GXR in adults regardless of ADHD subtype, age, or sex and suggest that careful monitoring for TEAEs and GXR dose optimization is considered for all patients, as needed.